2018
DOI: 10.1186/s41747-018-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated pineapple juice for visualisation of the oesophagus during magnetic resonance angiography before atrial fibrillation radiofrequency catheter ablation

Abstract: The purpose of this study was to compare in vitro pineapple juice and a solution of concentrated pineapple juice with a paramagnetic contrast agent in order to determine the feasibility of using the solution of concentrated pineapple juice in vivo for oesophagus visualisation at magnetic resonance angiography (MRA) before the radiofrequency catheter ablation procedure for atrial fibrillation. The pineapple juice was concentrated by a microwave heating evaporation process performed in a domestic microwave oven.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Pineapple juice has been shown effective as an oral contrast agent in magnetic resonance images, and, more recently, concentrated juices added with hydrogels [ 15 ] have been proposed to further enhance the contrast. However, so far, no detailed studies were performed on natural juices or on their derivatives to characterize the relaxation properties in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple juice has been shown effective as an oral contrast agent in magnetic resonance images, and, more recently, concentrated juices added with hydrogels [ 15 ] have been proposed to further enhance the contrast. However, so far, no detailed studies were performed on natural juices or on their derivatives to characterize the relaxation properties in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of distant metastases in EC is currently done with CT and 18 F-FDG-PET/CT. As previously mentioned, a 2004 meta-analysis evaluating the performance of 18 F-FDG-PET/CT for the diagnosis of distant metastases found a pooled sensitivity and specificity of 67% (95% CI: 58-76) and 97% (95% CI: 90-100), respectively [26]. In the 2008 meta-analysis by Van Vliet at al., sensitivities and specificities for the diagnosis of distant metastases were 71% (95% CI: 62-79) and 93% (95% CI: 89-97) for 18 F-FDG-PET/CT, 52% (95% CI: 33-71) and 91% (95% CI: 86-96) for CT [46].…”
Section: Metastases (M) Stagingmentioning
confidence: 95%
“…CT can be reliable when it comes to determining resectability by excluding high T-stages tumors [24,25]. 18 Ffluorodeoxyglucose ( 18 F-FDG) PET/CT has a limited role for T-staging due to its low spatial resolution and is mainly useful for the diagnosis of distant metastases [24,26]. Although the local and regional staging accuracy of EUS is greater than those of CT and PET [27], EUS is invasive and operator dependent, and sometimes limited by tumor stenosis [28].…”
Section: Initial Tumor (T) Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported the use of concentrated pineapple juice mixed with potatoe starch an as intraluminal agent for MRI examination of the esophagus. This mixture allowed a feasible and safe esophageal visualisation, with a patient acceptability and an image quality similar to paramagnetic contrast agents (24).…”
Section: Mri Protocols For the Esophagus (Figure 1)mentioning
confidence: 99%